2001
DOI: 10.1097/00006842-200101000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cadaveric Organ Donation on Taiwanese Donor Families During the First 6 Months After Donation

Abstract: Although all of the subjects reported that organ donation was the right decision, the decision to donate did not protect Taiwanese donor families from negative psychocognitive bereavement. The impacts of organ donation were affected by the subject's social cultural, spiritual, and legal context and the nature of their bereavement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 28 publications
0
37
0
3
Order By: Relevance
“…Sudden and unexpected death is identified as one of life's most stressful experiences 1 and, in such a complex situation, request for organ donation can be very difficult and traumatic. After a patient's demise, survivors feel overwhelmed with grief and cannot make such a profound decision as to donate an organ.…”
Section: Introductionmentioning
confidence: 99%
“…Sudden and unexpected death is identified as one of life's most stressful experiences 1 and, in such a complex situation, request for organ donation can be very difficult and traumatic. After a patient's demise, survivors feel overwhelmed with grief and cannot make such a profound decision as to donate an organ.…”
Section: Introductionmentioning
confidence: 99%
“…Relatives have been studied in relationship to circumstances that may enhance their acceptance of organ donation (5,(8)(9)(10), the stability of their decision (11), the impact of the decision 6 months after donation (12) and families' emotional characteristics and coping strategies (13).…”
Section: Introductionmentioning
confidence: 99%
“…This study identified the following sources of stress: concern and fear of the deformation of the donor's body, conflicts and family controversies about the decision to donate. Another factor recognized was the incomprehension of other relatives and friends, devaluing the act of donating, with the thought that they did it in exchange for the funeral aid, which results in emotional weariness for the people in charge of the donation as they feel pressured to give explanations (17) .…”
Section: Discussionmentioning
confidence: 99%